Economy and politics as an ideology: The problem of rationing health care - Puca, Antonio (Medicina e Morale, 1993)
The paper examines the problem of the allocation of resources in the health environment and evaluates the ethical and social implications. After a sociological analysis of health organization models, the author evaluates the problem from an ethical point of view underlining how the rationalization of the welfare system and services should come before the rationing of health care. But when this is necessary it's important to refer to certain criteria: the ethics of virtues, public procedures and equal distribution, a good medicai practice, the role of christians, bearing in mind that the physician cannot control the resources because of his moral obligations with respect to his patients.